THE INFLUENCE OF MARKETING MIX, SERVICE QUALITY AND CONSUMER SATISFACTION ON PRODUCT PURCHASE DECISIONS AT MALILI TEKNO - Yusnita Yusnita; Muhammad Aqsa; Rismawati Sudirman; Duriani Duriani, (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
This research aims to analyze the influence of marketing mix, service quality and consumer satisfaction on product purchasing decisions in Malili in East Luwu Regency. The marketing mix, which consists of product, price, promotion and distribution elements, is an important factor in determining consumer purchasing behavior. Service quality and consumer satisfaction are also considered crucial factors that can influence purchasing decisions. This research uses a quantitative approach with a survey method to collect data from Malili Tekno consumers. A total of 96 respondents were randomly selected to participate in this research. The data obtained was analyzed using the interference method to determine the influence between research variables. The research results show that simultaneously the marketing mix, service quality and consumer satisfaction have a positive and significant effect on product purchasing decisions at Malili Tekno. Partially, marketing mix and consumer satisfaction have a more dominant influence than service quality on purchasing decisions. These findings indicate that Malili Tekno needs to continue to optimize its marketing mix strategy and increase consumer satisfaction to encourage increased purchasing decisions.